Tropical Cyclones and Their Impact on Agriculture - Kumar, K. Ashok; Sudheer, K. V. S.; Anoosha, B.; Reddy, B. Sahadeva (Chronicle of Bioresource Management, 2024)
Tropical cyclones are predominant extreme weather events occurring most often across the Bay of Bengal, Arabian Sea, and the Indian Ocean. When these cyclones hit land, they demolish everything, causing floods, starvations, and fatalities. As a result of these cyclones, the coastal regions have faced numerous challenges over time. Despite their unpredictability, forecast techniques have made it possible to predict their occurrence time and range, which is very important in order to make the necessary preparations to face the monster. Farmers are used to depending on technologies that provide advice and projections to save them from the tedious work of farming; after all, agriculture field deals with all types of weather. In this regard, the present paper focuses on detailed information and a general understanding of cyclones, the distinction between cyclones and depressions, cyclone formation, its course, various categories into which these cyclones are divided, their impact in various ways, particularly on agriculture, and finally the remedies and crop-wise advisories to be followed during cyclone forecast to minimize agricultural losses.